Uncertainty in the drylands: Rethinking in/formal insurance from pastoral East Africa - Johnson, Leigh; Mohamed, Tahira Shariff; Scoones, Ian; Taye, Masresha (SAGE Publications, 2023)
Amidst climatic and economic volatility, agricultural development and climate adaptation policies have increasingly turned to weather microinsurance to manage uncertainties, particularly in dryland pastoral and agricultural settings. While the political embrace of insurance has been cause for concern amongst those who fear insurance will undermine embedded coping mechanisms and moral economies, economists have puzzled over low insurance adoption rates amongst target populations. This article argues for an approach that scrutinizes insurance in relation to dynamic social practices and norms for responding to uncertainty. We employ this approach to investigate pastoralists’ encounters with index-based livestock insurance in Northern Kenya and Southern Ethiopia. Drawing on interview, ethnographic, and survey data, we demonstrate how insurance is understood within larger moral economies and collective imaginaries for living with and managing uncertainty in the drylands. Relational understandings shape pastoralists’ participation in risk-sharing arrangements, collective and individual decisions about livestock insurance purchase, and eventual uses of insurance payouts. Payouts also support a broad array of social reproductive purposes and investments in social and political life. As we conclude, these findings upset the binary between formal and informal insurance, revealing how “formal” index insurance must be negotiated with embedded social affiliations, rights, obligations, and understandings of uncertainty.